Transcaval access for the emergency delivery of 5.0 liters per minute mechanical circulatory support in cardiogenic shock. Issue 3 (9th September 2020) - Afana, Majed; Altawil, Mahmoud; Basir, Mir; Alqarqaz, Mohammad; Alaswad, Khaldoon; Eng, Marvin; O'Neill, William W.; Lederman, Robert J.; Greenbaum, Adam B.
Abstract: Objectives: The purpose of this study was to describe the feasibility and early outcomes of transcaval access for delivery of emergency mechanical circulatory support (MCS) in cardiogenic shock. Background: Vascular access for implantation of MCS in patients with cardiogenic shock is often challenging due to peripheral arterial disease and vasoconstriction. Transcaval delivery of MCS may be an alternative. We describe a series of patients we implanted an Impella 5.0 device, on‐table without CT planning, through a percutaneous transcaval access route. Methods: Ten patients with progressive or refractory cardiogenic shock underwent Impella 5.0 implantation via transcaval access. Demographic, clinical and procedural variables and in‐hospital outcomes were collected. Results: All ten underwent emergency implantation of the 7 mm diameter Impella 5.0 device via transcaval access. Six were women, with median age of 55.5 years (range, 29–69). Cardiogenic shock was attributed to idiopathic nonischemic cardiomyopathy ( n = 4), myocarditis ( n = 2), ischemic cardiomyopathy ( n = 2), heart transplant rejection ( n = 1), and unknown etiology ( n = 1). Median duration of support was 92.1 hr (range, 21.2–165.4). Seven (70%) survived to device explant, with six (60%) surviving to access port closure and discharge. Among survivors, five recovered heart function and one received destination therapy left ventricular assist device. Conclusions: Transcaval access is feasible for emergency nonsurgical implantation of the Impella 5.0 device in cardiogenic shock with small or diseased iliofemoral arteries. This allows early institution of higher‐flow MCS than conventional femoral artery implantation of the 3.5 L Impella CP device, and enables a bridge‐to‐recovery or bridge‐to‐destination strategy.